Food and roosting habits of the lesser false vampire bat, Megaderma spasm a (Chiroptera Megadermatidae), in a Philippine lowland forest - Balete, Danilo S. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2010)
Two small colonies of the lesser false vampire bat, Megaderma spas a, roosting in a tree hollow and a small cave, were observed for a year in secondary lowland forest on Mt. Mailing, southern Luzon, Philippines. A total of 10 insect Orders comprised more than 99% of the prey culling a recovered from the roosts, indicating a predominantly insectivorous feeding habit of this species. Insects of the orders Coleoptera (beetles), Hemiptera (cicadas), and Orthoptera (katydids and crickets) represented close to 90% of the invertebrates consumed in the roosts. The predominance of these sound-producing, but generally cryptic and fairly well-hidden insects indicate that acoustic cues have an important influence in the food and foraging habits of M. Spasma. Diversity and abundance of insects consumed at the roosts were highest during the late dry season (April) to early dry season (February). Monitoring of the three hollow colony indicated regular foraging schedules, beginning shortly after sunset when resident bats left the roost and ending shortly before sunrise when they all returned for day roosting. Throughout the night individual bats returned to the three hollow periodically, often to consume their prey. More insects were brought to the roost and consumed during the first hour after emergence and the last hour prior day-roosting. Occasional carnivory by M. spasma was revealed by the presence of vertebrates, representing less than 1% of the annual number of prey consumed at the roosts.